Metabolomic and proteomic changes induced by growth inhibitory concentrations of copper in the biofilm-forming marine bacterium Pseudoalteromonas lipolytica. Issue 11 (7th October 2019) - Favre, Laurie; Ortalo-Magné, Annick; Kerloch, Lionel; Pichereaux, Carole; Misson, Benjamin; Briand, Jean-François; Garnier, Cédric; Culioli, Gérald
Abstract : Copper exposure in P. lipolytica TC8 revealed changes in cell membrane lipid composition and in copper cell homeostasis protein regulation. Abstract : Copper is an essential element for living cells but this metal is present in some marine environments at such high concentrations that it can be toxic for numerous organisms. In polluted areas, marine organisms may develop specific adaptive responses to prevent cell damage. To investigate the influence of copper on the metabolism of a single organism, a dual approach combining metabolomics and proteomics was undertaken on the biofilm-forming bacterial strain Pseudoalteromonas lipolytica TC8. In order to highlight differential adaptation according to the phenotype, the response of P. lipolytica TC8 to copper stress was studied in planktonic and biofilm culture modes under growth inhibitory copper concentrations. As expected, copper exposure led to the induction of defense and detoxification mechanisms. Specific metabolite and protein profiles were thus observed in each condition (planktonic vs. biofilm and control vs. copper-treated cultures). Copper exposure seems to induce drastic changes in the lipid composition of the bacterial cell membrane and to modulate the abundance of proteins functionally known to be involved in copper cell homeostasis in both planktonic and biofilm culture modes. Much more proteins differentially expressed after copper treatment were observed in biofilms than in planktonic cells, which could indicate a more heterogeneous response of biofilm cells to this metallic stress.